Treatment Options for Hydrocephalus Following Foramen Magnum Decompression for Chiari I Malformation: A Multicenter Study. Issue 4 (24th June 2019) - Bartoli, Andrea; Soleman, Jehuda; Berger, Assaf; Wisoff, Jeffrey H; Hidalgo, Eveline Teresa; Mangano, Francesco T; Keating, Robert F; Thomale, Ulrich W; Boop, Frederick; Roth, Jonathan; Constantini, Shlomi
Abstract: BACKGROUND: New-onset hydrocephalus following foramen magnum decompression (FMD) for Chiari I malformation (CM-I) is rare; its natural history and pathophysiology are poorly understood. OBJECTIVE: To describe a series of patients who developed hydrocephalus following FMD for CM-I, provide possible explanations of this phenomenon, and outline treatment options. METHODS: Out of patients undergoing FMD for CM-I from 6 different tertiary centers, we evaluated patients presenting with new-onset hydrocephalus following FMD. The retrospectively collected data included demographics, clinical, and radiological findings of the CM-I and hydrocephalus patients. Time from FMD and hydrocephalus onset, treatment, and surgical techniques were assessed. RESULTS: Of 549 patients who underwent FMD for CM-I, 28 (5.1%) subsequently developed hydrocephalus (18 females, 10 males), with a mean age of 11.7 ± 11.9 yr (range 6 mo to 52 yr). Hydrocephalus occurred on average 2.2 ± 2.6 mo after FMD (range 1 wk to 8 mo). Four patients did not have a violation of the arachnoid during the FMD surgery. Main presenting symptoms of hydrocephalus were headaches (17, 41%), vomiting (10, 24.4%), and cerebrospinal fluid (CSF) leak or pseudomeningocele (7, 17%). Overall, 23 patients (82.1%) underwent CSF shunting, 1 patient (3.5%) had an endoscopic third ventriculostomy, 3 patients (10.7%) temporary CSF diversion only, and 1 patient (3.5%) was treated with acetazolamide. CONCLUSION: Hydrocephalus following FMD for CM-I is uncommon, but important. Based on our series and literature review, its incidence is about 5% to 7% and most likely will require further surgery. Shunting appears to be the favored treatment option.